HA-APS (at) MSN-PDA-CS-mPEG nanoparticle and preparation method thereof
By performing multi-layer modification and loading of astragalus polysaccharides on mesoporous silica microspheres, HA-APS@MSN-PDA-CS-mPEG nanoparticles were prepared, which solved the poor targeting and side effects of Chinese herbal medicines in the treatment of lung cancer, and achieved efficient and targeted anti-tumor efficacy.
Patent Information
- Application Number
- CN202510030147.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
AI Technical Summary
The existing Chinese herbal medicines have problems such as poor targeting, difficulty in reaching the lesion site, and major side effects when treating lung cancer, and there are limitations in drug loading rate and stability of nanoparticles.
Mesoporous silica microspheres were used as carriers, and HA-APS@MSN-PDA-CS-mPEG nanoparticles were prepared through amino modification, PDA-CS-mPEG copolymer coating, hyaluronic acid modification and astragalus polysaccharide loading, which had pH sensitivity, long cycleability, good biocompatibility and photothermal effect.
It improves the targeting and anti-tumor efficacy of the drug, reduces the toxicity to normal tissues, enhances the anti-tumor effect under near-infrared irradiation, and is suitable for adjuvant treatment of lung cancer.
Smart Images

Figure CN119818531A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical nanomaterials, and specifically relates to HA-APS@MSN-PDA-CS-mPEG nanoparticles and a preparation method thereof. Background Art
[0002] Globally, cancer is the second leading cause of death. Lung cancer is one of the most common cancers, with about 25% of cancer deaths related to lung cancer. By 2040, the number of new cases worldwide will increase by nearly 50%. About one-third of lung cancer patients worldwide live in China. Lung cancer is mainly divided into non-small cell lung cancer and small cell lung cancer, which is more common in the elderly. In addition to typical respiratory symptoms such as sputum and hemoptysis, most lung cancer patients may also experience tumor metastasis, causing headaches, vomiting, abdominal pain, ascites, bone pain and other manifestations. For the treatment of lung cancer, modern medicine includes surgical resection, chemotherapy, radiotherapy, targeted therapy, chemical drugs and other methods. Traditional Chinese medicine has acupuncture, diet therapy, physical exercise, Chinese herbal medicine and other means. However, most lung cancer patients are older, and surgery, chemotherapy, radiotherapy and other methods are bound to cause great damage to the patient's body, and have large toxic side effects, and cannot prolong survival and improve the quality of life; Traditional Chinese medicine has limited therapeutic effects on cancer, and there are problems such as complex ingredients and unclear mechanisms of action.
[0003] Astragalus is the root of Astragalus mongolica or Astragalus membranaceus, a plant of the genus Astragalus in the Leguminosae family. It is sweet in taste, slightly warm in nature, and enters the spleen and lung meridians. It is mainly used to treat spleen qi deficiency syndrome, lung qi deficiency syndrome, spontaneous sweating syndrome due to qi deficiency, qi and blood deficiency, ulcers that are difficult to heal or heal, or ulcers that are difficult to heal for a long time. Astragalus polysaccharide (APS) is the main component of Astragalus, which can be used as an immune promoter or regulator. It also has antiviral, anti-tumor, anti-aging, anti-radiation, anti-stress, and antioxidant effects. It can enhance the effect of anti-tumor drugs when used with them, and it has an auxiliary effect on the treatment of cancer. It can reduce some side effects while enhancing the efficacy.
[0004] In actual clinical treatment, the therapeutic effect of Chinese herbal medicines is still weak because they lack the ability to specifically target tumor cells, are easily cleared by the bloodstream, and it is difficult for drugs to reach the lesion site, which hinders the therapeutic effect of cancer. Many nanoparticles have been developed as drug delivery systems, which to a certain extent improve the specificity and anti-tumor efficacy of drugs by enhancing the permeability and retention (EPR) effect. After several years of research and development, nanoparticles (NPs) have been proven to have great potential application value.
[0005] MSNs have attracted widespread attention in recent years as potential drug delivery carriers. They have the characteristics of controllable size and morphology, high specific surface area, good biocompatibility and easy surface functional modification. However, they still have many limitations in drug loading rate and may also lead to premature drug release and cytotoxicity.
[0006] In view of this, the present invention proposes a new MSN nano-drug delivery system loaded with astragalus polysaccharide and a preparation method thereof. The prepared HA-APS@MSN-PDA-CS-mPEG nanoparticles are pH-sensitive, long-circulating, good biocompatibility and photothermal effect nano-drug delivery systems, which can be used for the adjuvant treatment of lung cancer. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing HA-APS@MSN-PDA-CS-mPEG nanoparticles, using mesoporous silica as a nanocarrier, and coating the copolymer micelles formed by PDA, CS, and mPEG on the surface of silica spheres, followed by encapsulating HA modified with differentiation cluster protein C4DD, and finally loading astragalus polysaccharide, and utilizing layer-by-layer structural modification to obtain a nano drug delivery system with a targeted effect, and the preparation method has high universality.
[0008] In order to achieve the above purpose, the technical solution adopted is:
[0009] A method for preparing HA-APS@MSN-PDA-CS-mPEG nanoparticles comprises the following steps:
[0010] (1) Preparation of mesoporous silica microspheres;
[0011] (2) Amino modification: the mesoporous silica microspheres are subjected to amino modification to obtain MSN-NH2;
[0012] (3) coating the MSN-NH2 with a PDA-CS-mPEG copolymer to obtain MSN-PDA-CS-mPEG;
[0013] (4) Hyaluronic acid modification: The MSN-PDA-CS-mPEG is modified with hyaluronic acid to obtain HA@MSN-PDA-CS-mPEG;
[0014] (5) Loading astragalus polysaccharide: The HA@MSN-PDA-CS-mPEG and astragalus polysaccharide are mixed evenly in an aqueous solution, stirred and reacted for 22-26 hours in a dark environment, and then solid-liquid separation, centrifugal washing, and freeze-drying are performed to obtain the HA-APS@MSN-PDA-CS-mPEG nanoparticles.
[0015] Furthermore, the process of preparing mesoporous silica microspheres in step (1) is as follows: dissolving CTAB and ammonia water in water until clear, adding ethanol solution and stirring until uniformly mixed, then dropping tetraethyl silicate and reacting for at least 48 hours, adding methanol at 75-85° C. to promote precipitation production, solid-liquid separation, centrifugal washing, vacuum drying, calcination, and cooling to room temperature;
[0016] The amino modification process in step (2) is as follows: dissolving the mesoporous silica microspheres in toluene, adding 3-aminopropyltriethoxysilane, mixing evenly, adding triethylamine, reacting at 110-130° C. for at least 5 hours, separating the solid from the liquid, washing by centrifugation, and freeze-drying;
[0017] The coating process in step (3) is as follows: dissolving the PDA-CS-mPEG copolymer and the MSN-NH2 in water, stirring and reacting in the dark, and then separating the solid from the liquid, washing by centrifugation, and freeze-drying.
[0018] Furthermore, in the step (2), the mass volume ratio of the mesoporous silica microspheres to toluene and 3-aminopropyltriethoxysilane is 390-410 mg: 40 mL: 1.8 ml;
[0019] In the step (3), the mass ratio of MSN-NH2 and PDA-CS-mPEG copolymer is 1:0.8-1.2.
[0020] Furthermore, in the step (2), the mass volume ratio of the mesoporous silica microspheres to toluene and 3-aminopropyltriethoxysilane is 400 mg: 40 mL: 1.8 ml;
[0021] In the step (3), the mass ratio of MSN-NH2 and PDA-CS-mPEG copolymer is 1:1.
[0022] Furthermore, the preparation method of the PDA-CS-mPEG copolymer in step (3) is: after 1-hydroxybenzotriazole and 1-ethyl-(3-dimethyl-amino-propyl)carbodiimide are uniformly dispersed in water, PDA, CS, and mPEG-COOH are added, and after stirring the reaction in the dark, dichloromethane is used as an extractant for extraction, and then rotary evaporation and freeze drying are performed at 55-65°C.
[0023] Furthermore, the mass ratio of 1-hydroxybenzotriazole, 1-ethyl-(3-dimethyl-amino-propyl)carbodiimide, PDA, CS, and mPEG-COOH is 1:2:1:1:6.
[0024] Furthermore, the process of hyaluronic acid modification in step (4) is as follows: adding the MSN-PDA-CS-mPEG to the activated hyaluronic acid solution, stirring at room temperature for 23-26 hours, separating the solid and liquid, washing by centrifugation, and drying in vacuo;
[0025] The preparation method of the activated hyaluronic acid solution is as follows: hyaluronic acid is uniformly dispersed in PBS buffer, and EDC and NHS are added to activate it;
[0026] In the step (5), the mass ratio of HA@MSN-PDA-CS-mPEG to astragalus polysaccharide is 1.4-2:2.
[0027] Furthermore, in the step (4), the mass ratio of hyaluronic acid to MSN-PDA-CS-mPEG is 1.5:0.30-0.4;
[0028] In the step (5), the mass ratio of HA@MSN-PDA-CS-mPEG to astragalus polysaccharide is 1.9:2.
[0029] Furthermore, in the step (4), the mass ratio of hyaluronic acid to MSN-PDA-CS-mPEG is 1.5:0.35.
[0030] Another object of the present invention is to provide a HA-APS@MSN-PDA-CS-mPEG nanoparticle, which is prepared by the above-mentioned preparation method, has pH sensitivity, long circulation, good biocompatibility and photothermal effect, has a good tumor killing effect, and the anti-tumor effect is enhanced under near-infrared irradiation, and can be used for the adjuvant treatment of lung cancer.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] Astragalus polysaccharide is one of the main active ingredients of Astragalus. It is a water-soluble heteropolysaccharide extracted, concentrated and purified from the dried roots of Astragalus mongolica or Astragalus membranaceus. Its molecular formula is C 10 H7ClN2O2S is light yellow, fine powder, uniform and free of impurities, hygroscopic, and can be used as an immunostimulant or regulator, with antiviral, anti-tumor, anti-aging, anti-radiation, anti-stress, and anti-oxidation effects. APS has been verified to have a killing effect on A549 lung cancer cells, but it still has the problems of poor stability, low utilization rate, and poor targeting. Based on this, the present invention proposes a HA-APS@MSN-PDA-CS-mPEG nanoparticle and a preparation method thereof, and prepares a new nano drug delivery system to improve its existing defects. The nano drug delivery system is based on mesoporous silica microspheres (MSN) as carriers, and the active ingredient of the Chinese medicine Astragalus is loaded on the carrier. Astragalus polysaccharide (APS), the surface is modified with a copolymer of polydopamine (PDA), chitosan (CS), polyethylene glycol (mPEG) and hyaluronic acid (HA), and the nano drug delivery system has the following advantages:
[0033] 1. In the technical solution of the present invention, a simple method is used to prepare honeycomb mesoporous silica with a high specific surface area, which has a uniformly arranged pore structure and can better load drugs.
[0034] 2. In the technical solution of the present invention, the drug delivery system is modified by using a cross-linking agent PDA-CS-mPEG with multi-level responsiveness to prepare nanoparticles with photothermal effect, pH sensitivity, high biocompatibility, transport capacity, and long circulation.
[0035] 3. In the technical solution of the present invention, the surface coating of hyaluronic acid (HA) enables the drug delivery system to escape capture by the immune system, thereby increasing the circulation time in the body, which is beneficial to improving the active targeting of the drug, while enhancing the killing effect on tumor cells and reducing toxicity to normal tissues.
[0036] 4. In the technical solution of the present invention, during the drug loading process of the HA@MSN-PDA-CS-mPEG nano-drug delivery system on APS, the pore size of the nanoparticles is about 7 nm, and the drug molecules can be directly incorporated into the pores for loading.
[0037] 5. In the technical scheme of the present invention, the prepared HA-APS@MSN-PDA-CS-mPEG nanoparticles have strong and uniform encapsulation. Under the simulated tumor microenvironment, the drug release rate reaches 64.31%, which has a good killing effect on tumors. The anti-tumor effect is enhanced under near-infrared irradiation. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 SEM scans of MSN, MSN-PDA-CS-mPEG, and HA@MSN-PDA-CS-mPEG;
[0039] Figure 2 TEM scans of MSN, MSN-PDA-CS-mPEG, and HA@MSN-PDA-CS-mPEG;
[0040] Figure 3 BET and BJH diagrams of MSN, MSN-NH2, MSN-PDA-CS-mPEG and HA@MSN-PDA-CS-mPEG of the present invention;
[0041] Figure 4 Particle size, Zeta potential, and TGA graph of MSN, MSN-NH2, MSN-PDA-CS-mPEG, and HA@MSN-PDA-CS-mPEG of the present invention;
[0042] Figure 5 The infrared spectra of HA, APS, PDA, CS, mPEG, MSN, MSN-NH2, MSN-PDA-CS-mPEG, HA@MSN-PDA-CS-mPEG, and HA-APS@MSN-PDA-CS-mPEG;
[0043] Figure 6 a and b are the UV spectrum and standard curve of APS, respectively;
[0044] Figure 7 a and b are drug loading diagrams of HA@MSN-PDA-CS-mPEG of the present invention;
[0045] Figure 8 a and b are the drug release of HA-APS@MSN-PDA-CS-mPEG at different pH under and without infrared irradiation, respectively;
[0046] Fig. 9 is the photothermal performance diagram of nanoparticles;
[0047] Fig.10 is the hemolytic performance diagram of the nanoparticles;
[0048] Fig.11 a and b are the cytotoxicity graphs of MSN, HA-@MSN-PDA-CS-mPEG, HA-APS@MSN-PDA-CS-mPEG and HA-APS@MSN-PDA-CS-mPEG+NIR. DETAILED DESCRIPTION
[0049] In order to further illustrate the HA-APS@MSN-PDA-CS-mPEG nanoparticles and preparation methods thereof of the present invention and achieve the intended purpose of the invention, the following is a detailed description of the HA-APS@MSN-PDA-CS-mPEG nanoparticles and preparation methods thereof, their specific implementation methods, structures, features and effects proposed according to the present invention, in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0050] The following will further introduce the HA-APS@MSN-PDA-CS-mPEG nanoparticles and the preparation method thereof in detail in conjunction with specific embodiments:
[0051] The therapeutic effect of traditional Chinese medicine on tumors is very limited, and there are defects such as poor stability, easy deformation and inactivation, short biological half-life, low bioavailability, and difficulty in penetrating physiological barriers. Nanomedicine developed by nanomedicine can solve these defects and improve drug utilization. The typical means of modern medicine for treating tumors are surgical resection, chemotherapy and radiotherapy. For cancer patients, toxic side effects, postoperative adverse reactions, limited therapeutic effects, etc. have brought great pain to patients. Nanomedicine developed by nanomedicine can effectively improve the above-mentioned defects and has become an effective measure for treating cancer, showing obvious advantages in improving efficacy and safety. Based on this, a HA-APS@MSN-PDA-CS-mPEG nanoparticle and a preparation method thereof are proposed in the present invention. The technical solution of the present invention is:
[0052] A method for preparing HA-APS@MSN-PDA-CS-mPEG nanoparticles comprises the following steps:
[0053] (1) Preparation of mesoporous silica microspheres;
[0054] (2) Amino modification: the mesoporous silica microspheres are subjected to amino modification to obtain MSN-NH2;
[0055] (3) coating the MSN-NH2 with a PDA-CS-mPEG copolymer to obtain MSN-PDA-CS-mPEG;
[0056] (4) Hyaluronic acid modification: The MSN-PDA-CS-mPEG is modified with hyaluronic acid to obtain HA@MSN-PDA-CS-mPEG;
[0057] (5) Loading astragalus polysaccharide: The HA@MSN-PDA-CS-mPEG and astragalus polysaccharide are mixed evenly in an aqueous solution, stirred and reacted for 22-26 hours in a dark environment, and then solid-liquid separation, centrifugal washing, and freeze-drying are performed to obtain the HA-APS@MSN-PDA-CS-mPEG nanoparticles.
[0058] In the above technical scheme, mesoporous silica microspheres (MSN) are used as carriers, and astragalus polysaccharide (APS), the active ingredient of the traditional Chinese medicine Astragalus, is loaded on the carrier. The surface is modified with copolymers of polydopamine (PDA), chitosan (CS), polyethylene glycol (mPEG) and hyaluronic acid (HA) to prepare a nano drug delivery system with pH sensitivity, long circulation, good biocompatibility and photothermal effect.
[0059] Photothermal therapy (PTT) is a new non-chemotherapeutic intervention method that induces apoptosis of tumor cells by generating high temperature through local near-infrared laser irradiation. PDA is a typical nanomaterial suitable for PTT, with excellent biocompatibility and degradability. In addition, PDA has ideal near-infrared photothermal conversion efficiency and is an effective photothermal therapeutic agent. CS has multiple properties such as antibacterial activity, excellent biocompatibility and hydrophilicity. Its molecular chain contains a large number of -NH2 groups and has good pH sensitivity. PEG modification makes nanocarriers have better water solubility and biocompatibility, and improves the transport capacity of nanoparticles.
[0060] HA has good biodegradability and biocompatibility, and can prevent the adsorption of most blood proteins on the surface of nanoparticles, thereby prolonging the circulation time of drug-delivered nanoparticles. HA is overexpressed in the tumor microenvironment, and the differentiation protein CD44 cluster is the main receptor for HA. Therefore, HA-modified nanocarriers can quickly enter cells through the endocytic pathway of CD44 delivery, specifically increase drug accumulation in cancer cells that overexpress CD44, and thus improve the anti-tumor efficacy of chemotherapeutic drugs.
[0061] Preferably, the process of preparing mesoporous silica microspheres in step (1) is as follows: dissolving CTAB and ammonia water in water until clear, adding ethanol solution and stirring until uniformly mixed, then dropping tetraethyl silicate and reacting for at least 48 hours, adding methanol at 75-85° C. to promote precipitation, solid-liquid separation, centrifugal washing, vacuum drying, calcination, and cooling to room temperature;
[0062] The amino modification process in step (2) is as follows: dissolving the mesoporous silica microspheres in toluene, adding 3-aminopropyltriethoxysilane, mixing evenly, adding triethylamine, reacting at 110-130° C. for at least 5 hours, separating the solid from the liquid, washing by centrifugation, and freeze-drying;
[0063] The coating process in step (3) is as follows: dissolving the PDA-CS-mPEG copolymer and the MSN-NH2 in water, stirring and reacting in the dark, and then separating the solid from the liquid, washing by centrifugation, and freeze-drying.
[0064] Further preferably, the mass volume ratio of the mesoporous silica microspheres to toluene and 3-aminopropyltriethoxysilane in step (2) is 390-410 mg: 40 mL: 1.8 ml;
[0065] In the step (3), the mass ratio of MSN-NH2 and PDA-CS-mPEG copolymer is 1:0.8-1.2.
[0066] Further preferably, in the step (2), the mass volume ratio of the mesoporous silica microspheres to toluene and 3-aminopropyltriethoxysilane is 400 mg: 40 mL: 1.8 ml;
[0067] In the step (3), the mass ratio of MSN-NH2 and PDA-CS-mPEG copolymer is 1:1.
[0068] Preferably, the preparation method of the PDA-CS-mPEG copolymer in step (3) is: after 1-hydroxybenzotriazole and 1-ethyl-(3-dimethyl-amino-propyl)carbodiimide are uniformly dispersed in water, PDA, CS, and mPEG-COOH are added, and after stirring the reaction in the dark, dichloromethane is used as an extractant for extraction, and then rotary evaporation and freeze drying are performed at 55-65°C.
[0069] Further preferably, the mass ratio of 1-hydroxybenzotriazole, 1-ethyl-(3-dimethyl-amino-propyl)carbodiimide, PDA, CS, and mPEG-COOH is 1:2:1:1:6.
[0070] Preferably, the process of hyaluronic acid modification in step (4) is: adding the MSN-PDA-CS-mPEG to the activated hyaluronic acid solution, stirring at room temperature for 23-26 hours, separating the solid and liquid, washing by centrifugation, and drying in vacuo;
[0071] The preparation method of the activated hyaluronic acid solution is as follows: hyaluronic acid is uniformly dispersed in PBS buffer, and EDC and NHS are added to activate it;
[0072] In the step (5), the mass ratio of HA@MSN-PDA-CS-mPEG to astragalus polysaccharide is 1.4-2:2.
[0073] Further preferably, in the step (4), the mass ratio of hyaluronic acid to MSN-PDA-CS-mPEG is 1.5:0.30-0.4;
[0074] In the step (5), the mass ratio of HA@MSN-PDA-CS-mPEG to astragalus polysaccharide is 1.9:2.
[0075] Further preferably, in the step (4), the mass ratio of hyaluronic acid to MSN-PDA-CS-mPEG is 1.5:0.35.
[0076] Example 1.
[0077] The specific steps are as follows:
[0078] (1) Preparation of mesoporous silica microspheres
[0079] Add 1.44 g CTAB and 15 mL ammonia water into 460 mL ultrapure water, dissolve at 37 °C until clear, then add 230 mL ethanol and 230 mL ultrapure water and continue stirring for 1 h.
[0080] Then, 2 mL of tetraethyl silicate was slowly added dropwise, and the reaction was stirred at 400 rpm for 48 h. After 150 mL of methanol was added at 80°C to promote the formation of precipitation, the mixture was centrifuged at 10,000 rpm for 10 min to obtain a precipitate. The precipitate was centrifuged and washed with water and ethanol as detergents, three times each, and each centrifugation was centrifuged at 10,000 r / min for 10 min. The washed precipitate was collected and vacuum dried at 50°C overnight.
[0081] The dried product was placed in a muffle furnace for calcination. The settings of the muffle furnace were as follows: a starting temperature of 30°C, an end temperature of 550°C, a heating rate of 2°C / min, a heating time of 260min, a holding temperature of 550°C, a holding time of 240min, and cooled to room temperature to obtain the product MSN.
[0082] (2) Aminated mesoporous silica
[0083] 100 mg of MSN was dissolved in 10 mL of toluene, 0.45 mL of 3-aminopropyltriethoxysilane was added, and after ultrasonic dispersion, 0.9 mL of triethylamine was added as a promoter (which was beneficial to the reaction). The suspension was fully reacted at 120 ° C for 5 h, and the precipitate was collected by centrifugation. After washing with acetone several times, it was freeze-dried overnight to obtain MSN-NH2.
[0084] (3) Preparation of PDA-CS-mPEG
[0085] To 20 mL of ultrapure water, 50 mg of 1-hydroxybenzotriazole (HoBt) and 100 mg of 1-ethyl-(3-dimethyl-amino-propyl)carbodiimide (EDC) were added and ultrasonically dispersed uniformly. PDA (50 mg), CS (50 mg) and mPEG-COOH (300 mg) were added to the mixed solution and stirred for 24 h in the dark. Dichloromethane (40 mL) was used as the extractant and extracted three times by rotary evaporation at 60 °C. The mixture was freeze-dried overnight to obtain PDA-CS-mPEG copolymer.
[0086] (4) Preparation of MSN-PDA-CS-mPEG
[0087] Weigh 500 mg of MSN-NH2 prepared in step (3) and 500 mg of PDA-CS-mPEG prepared in step (2) and dissolve them in 1000 mL of ultrapure water, stir for 24 h in dark, and centrifuge at 10000 rpm for 10 min to obtain a precipitate. The precipitate is centrifuged and washed with ultrapure water and anhydrous ethanol as detergents, and the ultrapure water and anhydrous ethanol are washed three times each, and each centrifugation is centrifuged at a speed of 10000 r / min for 10 min. The washed precipitate is collected and freeze-dried overnight to obtain MSN-PDA-CS-mPEG.
[0088] (5) Preparation of HA@MSN-PDA-CS-mPEG
[0089] 1.5 g of HA was weighed and dissolved in 1000 mL of PBS buffer (pH = 5.0), ultrasonically dispersed evenly, stirred for 1 h, 8.83 g of EDC and 5.32 g of NHS were added and stirred for 2 h, 350 mg of MSN-PDA-CS-mPEG prepared in step (4) was weighed and added to the mixture, stirred for 24 h under light-proof conditions, and centrifuged at 10000 rpm for 10 min to obtain a precipitate. The precipitate was centrifuged and washed, using water and ethanol as detergents, and washed three times with water and ethanol respectively, each centrifuged at a speed of 10000 r / min for 10 min, and the washed precipitate was collected and freeze-dried overnight to obtain HA@MSN-PDA-CS-mPEG.
[0090] (6) 190 mg of astragalus polysaccharide (APS) and 200 mg of the HA-APS@MSN-PDA-CS-mPEG nanocarrier obtained in step (5) were added to 100 mL of ultrapure water, and the mixture was uniformly dispersed by ultrasonication for 40 min. The mixture was stirred at 700 r / min in the dark at room temperature for 24 h, and centrifuged at 10,000 rpm for 10 min to obtain a precipitate. The precipitate was washed by centrifugation, using ultrapure water and anhydrous ethanol as detergents, and washed three times with ultrapure water and anhydrous ethanol respectively, and each centrifugation was centrifuged at 10,000 r / min for 10 min. After washing free drugs and surface adsorbed drugs with ultrapure water and anhydrous ethanol, the washed product was freeze-dried overnight to obtain HA-APS@MSN-PDA-CS-mPEG nanoparticles.
[0091] Example 2.
[0092] The specific steps are as follows:
[0093] (1) Preparation of mesoporous silica microspheres
[0094] Add 1.44 g CTAB and 15 mL ammonia water into 460 mL ultrapure water, dissolve at 37 °C until clear, then add 230 mL ethanol and 230 mL ultrapure water and continue stirring for 1 h.
[0095] Then, 2 mL of tetraethyl silicate was slowly added dropwise, and the reaction was stirred at 400 rpm for 48 h. After 150 mL of methanol was added at 75°C to promote the formation of precipitation, the mixture was centrifuged at 10,000 rpm for 10 min to obtain a precipitate. The precipitate was centrifuged and washed with water and ethanol as detergents, three times each, and each centrifugation was performed at 10,000 r / min for 10 min. The washed precipitate was collected and vacuum dried at 50°C overnight.
[0096] The dried product was placed in a muffle furnace for calcination. The settings of the muffle furnace were as follows: a starting temperature of 30°C, an end temperature of 550°C, a heating rate of 2°C / min, a heating time of 260min, a holding temperature of 550°C, a holding time of 240min, and cooled to room temperature to obtain the product MSN.
[0097] (2) Aminated mesoporous silica
[0098] 97.5 mg of MSN was dissolved in 10 mL of toluene, 0.45 mL of 3-aminopropyltriethoxysilane was added, and 0.9 mL of triethylamine was added as a promoter after ultrasonic dispersion. The suspension was fully reacted at 110 °C for 6 h, and the precipitate was collected by centrifugation, washed with acetone several times, and freeze-dried overnight to obtain MSN-NH2.
[0099] (3) Preparation of PDA-CS-mPEG
[0100] To 20 mL of ultrapure water, 50 mg of 1-hydroxybenzotriazole (HoBt) and 100 mg of 1-ethyl-(3-dimethyl-amino-propyl)carbodiimide (EDC) were added and ultrasonically dispersed uniformly. PDA (50 mg), CS (50 mg) and mPEG-COOH (300 mg) were added to the mixed solution and stirred for 24 h in the dark. Dichloromethane (40 mL) was used as the extractant and extracted three times by rotary evaporation at 60 °C. The mixture was freeze-dried overnight to obtain PDA-CS-mPEG copolymer.
[0101] (4) Preparation of MSN-PDA-CS-mPEG
[0102] Weigh 500 mg of MSN-NH2 prepared in step (3) and 400 mg of PDA-CS-mPEG prepared in step (2) and dissolve them in 1000 mL of ultrapure water, stir in dark for 24 h, and centrifuge at 10000 rpm for 10 min to obtain a precipitate. The precipitate is centrifuged and washed with ultrapure water and anhydrous ethanol as detergents, and the ultrapure water and anhydrous ethanol are washed three times each, and each centrifugation is centrifuged at a speed of 10000 r / min for 10 min. The washed precipitate is collected and freeze-dried overnight to obtain MSN-PDA-CS-mPEG.
[0103] (5) Preparation of HA@MSN-PDA-CS-mPEG
[0104] 1.5 g of HA was weighed and dissolved in 1000 mL of PBS buffer (pH = 5.0), ultrasonically dispersed uniformly, stirred for 1 h, 8.83 g of EDC and 5.32 g of NHS were added and stirred for 2 h, 300 mg of MSN-PDA-CS-mPEG prepared in step (4) was weighed and added to the mixture, stirred for 23 h under light-proof conditions, and centrifuged at 10000 rpm for 10 min to obtain a precipitate. The precipitate was centrifuged and washed, using water and ethanol as detergents, and washed three times with water and ethanol respectively, each centrifuged at a speed of 10000 r / min for 10 min, and the washed precipitate was collected and freeze-dried overnight to obtain HA@MSN-PDA-CS-mPEG.
[0105] (6) 190 mg of astragalus polysaccharide (APS) and 200 mg of the HA-APS@MSN-PDA-CS-mPEG nanocarrier obtained in step (5) were added to 100 mL of ultrapure water, and the mixture was uniformly dispersed by ultrasonication for 40 min. The mixture was stirred at 700 r / min in the dark at room temperature for 22 h, and centrifuged at 10,000 rpm for 10 min to obtain a precipitate. The precipitate was centrifuged and washed with ultrapure water and anhydrous ethanol as detergents, and the ultrapure water and anhydrous ethanol were washed three times each, and each centrifugation was centrifuged at 10,000 r / min for 10 min. After washing away free drugs and surface adsorbed drugs with ultrapure water and anhydrous ethanol, the washed product was freeze-dried overnight to obtain HA-APS@MSN-PDA-CS-mPEG nanoparticles.
[0106] Example 3.
[0107] The specific steps are as follows:
[0108] (1) Preparation of mesoporous silica microspheres
[0109] Add 1.44 g CTAB and 15 mL ammonia water into 460 mL ultrapure water, dissolve at 37 °C until clear, then add 230 mL ethanol and 230 mL ultrapure water and continue stirring for 1 h.
[0110] Then, 2 mL of tetraethyl silicate was slowly added dropwise, and the reaction was stirred at 400 rpm for 48 h. After 150 mL of methanol was added at 85 °C to promote the formation of precipitation, the mixture was centrifuged at 10,000 rpm for 12 min to obtain a precipitate. The precipitate was centrifuged and washed with water and ethanol as detergents, and washed with water and ethanol three times each, with each centrifugation at 10,000 r / min for 15 min. The washed precipitate was collected and vacuum dried at 50 °C overnight.
[0111] The dried product was placed in a muffle furnace for calcination. The settings of the muffle furnace were as follows: a starting temperature of 30°C, an end temperature of 550°C, a heating rate of 2°C / min, a heating time of 260min, a holding temperature of 550°C, a holding time of 240min, and cooled to room temperature to obtain the product MSN.
[0112] (2) Aminated mesoporous silica
[0113] 102.5 mg of MSN was dissolved in 10 mL of toluene, 0.45 mL of 3-aminopropyltriethoxysilane was added, and 0.9 mL of triethylamine was added as a promoter after ultrasonic dispersion. The suspension was fully reacted at 130 °C for 5 h, and the precipitate was collected by centrifugation, washed with acetone several times, and freeze-dried overnight to obtain MSN-NH2.
[0114] (3) Preparation of PDA-CS-mPEG
[0115] To 20 mL of ultrapure water, 50 mg of 1-hydroxybenzotriazole (HoBt) and 100 mg of 1-ethyl-(3-dimethyl-amino-propyl)carbodiimide (EDC) were added and ultrasonically dispersed uniformly. PDA (50 mg), CS (50 mg) and mPEG-COOH (300 mg) were added to the mixed solution and stirred for 24 h in the dark. Dichloromethane (40 mL) was used as the extractant and extracted three times by rotary evaporation at 60 °C. The mixture was freeze-dried overnight to obtain PDA-CS-mPEG copolymer.
[0116] (4) Preparation of MSN-PDA-CS-mPEG
[0117] Weigh 500 mg of MSN-NH2 prepared in step (3) and 600 mg of PDA-CS-mPEG prepared in step (2) and dissolve them in 1000 mL of ultrapure water, stir in dark for 26 h, and centrifuge at 10000 rpm for 15 min to obtain a precipitate. The precipitate is centrifuged and washed with ultrapure water and anhydrous ethanol as detergents, and the ultrapure water and anhydrous ethanol are washed 3 times each, and each centrifugation is centrifuged at a speed of 10000 r / min for 10 min. The washed precipitate is collected and freeze-dried overnight to obtain MSN-PDA-CS-mPEG.
[0118] (5) Preparation of HA@MSN-PDA-CS-mPEG
[0119] 1.5 g of HA was weighed and dissolved in 1000 mL of PBS buffer (pH = 5.0), ultrasonically dispersed uniformly, stirred for 1 h, 8.83 g of EDC and 5.32 g of NHS were added and stirred for 2 h, 400 mg of MSN-PDA-CS-mPEG prepared in step (4) was weighed and added to the mixture, stirred for 26 h under light-proof conditions, and centrifuged at 10000 rpm for 10 min to obtain a precipitate. The precipitate was centrifuged and washed, using water and ethanol as detergents, and washed 3 times with water and ethanol respectively, each centrifuged at a speed of 10000 r / min for 12 min, and the washed precipitate was collected and freeze-dried overnight to obtain HA@MSN-PDA-CS-mPEG.
[0120] (6) 190 mg of astragalus polysaccharide (APS) and 200 mg of the HA-APS@MSN-PDA-CS-mPEG nanocarrier obtained in step (5) were added to 100 mL of ultrapure water, and the mixture was uniformly dispersed by ultrasonication for 40 min. The mixture was stirred at 700 r / min in the dark at room temperature for 24 h, and centrifuged at 10,000 rpm for 15 min to obtain a precipitate. The precipitate was centrifuged and washed with ultrapure water and anhydrous ethanol as detergents, and the ultrapure water and anhydrous ethanol were washed three times each, and each centrifugation was centrifuged at 10,000 r / min for 10 min. After washing away free drugs and surface adsorbed drugs with ultrapure water and anhydrous ethanol, the washed product was freeze-dried overnight to obtain HA-APS@MSN-PDA-CS-mPEG nanoparticles.
[0121] Example 4: Physical Characterization
[0122] (1) SEM test
[0123] Method: Take a small amount of MSN, MSN-PDA-CS-mPEG, and HA@MSN-PDA-CS-mPEG prepared in Example 1, dissolve them in ethanol and disperse them ultrasonically, drop the samples on the silicon wafer with a 200μl pipette, attach the silicon wafers to the conductive glue to prepare samples and mark them, where sample No. 1 is MSN, sample No. 2 is MSN-PDA-CS-mPEG, and sample No. 3 is HA@MSN-PDA-CS-mPEG. The conductivity of the material is enhanced by 30s gold plating to facilitate obtaining better morphological features in SEM, and then put it into the SEM observation room for observation. After finding the sample at low magnification, the appropriate area can be selected for observation and photography at a magnification.
[0124] SEM test results: The results are as follows Figure 1 shown. Figure 1a is a scanning electron microscope (SEM) image of MSN 1μm; 1b is a scanning electron microscope (SEM) image of MSN-PDA-CS-mPEG 1μm, and 1c is a scanning electron microscope (SEM) image of HA@MSN-PDA-CS-mPEG 1μm. The SEM images show that the structure of MSN has not changed significantly before and after coating, and the original spherical structure is still maintained.
[0125] (2) TEM test
[0126] Method: Take a small amount of MSN, MSN-PDA-CS-mPEG and HA@MSN-PDA-CS-mPEG prepared in Example 1, dissolve them in ethanol and disperse them ultrasonically, and drop the samples on the copper mesh with a 10μl pipette, where sample No. 1 is MSN, sample No. 2 is MSN-PDA-CS-mPEG, and sample No. 3 is HA@MSN-PDA-CS-mPEG. Scan and observe with a TEM transmission electron microscope, find a suitable sample at a low magnification, and observe and take pictures at a high magnification.
[0127] TEM test results: The results are as follows Figure 2 shown. Figure 2 a is a transmission electron microscope (TEM) image of MSN 100nm; 2b is a transmission electron microscope (TEM) image of MSN-PDA-CS-mPEG 100nm, and 2c is a transmission electron microscope (TEM) image of HA@MSN-PDA-CS-mPEG 100nm. It can be seen from the TEM image that the prepared mesoporous silica is honeycomb-shaped, with relatively uniform particle size and pore size, and its pores are evenly distributed and clearly visible. After grafting the PDA-CS-mPEG crosslinker, the surface becomes rough from relatively smooth, and the original pores are covered, but the original uniform spherical structure is maintained. After the surface is coated with HA, the boundary becomes exceptionally clear again, the surface is smooth, and the uniform spherical structure is still maintained.
[0128] Example 5: Pore Size Analysis
[0129] Methods: Nitrogen adsorption-desorption isotherms were measured by A500 instrument (Mike, USA), and the specific surface area was calculated from the adsorption data in the low pressure range using the Brunauer-Emmett-Teller (BET) model, and the pore size was determined according to the Barrett Joyner-Halenda (BJH) method.
[0130] The obtained data were processed by Origin software, and finally the BET graphs of MSN, MSN-NH2, MSN-PDA-CS-mPEG, and HA@MSN-PDA-CS-mPEG prepared in Example 1 were obtained.
[0131] Results: Figure 3 As shown in the figure, a, b, c, and d are the N2 adsorption-desorption curves of MSN, MSN-NH2, MSN-PDA-CS-mPEGMSN, and HA@MSN-PDA-CS-mPEG, respectively (the inset is the corresponding pore size distribution curve). MSN showed a typical Langmuir IV type hysteresis loop before and after modification, indicating that the material has a mesoporous structure. After amination, the pore size of MSN changed from 3.0515 nm to 3.6609 nm, with no significant change, while the specific surface area increased from 2031.4901 m 2 / g decreased to 13348m 2 / g, and the pore volume also increased from 1.159229cm 3 / g is reduced to 0.532800cm 3 / g. After PDA-CS-mPEG was grafted onto the surface of MSN, the surface became rough, a new pore structure was introduced, and the specific surface area was reduced to 576.2436 m 2 / g, while the pore diameter and pore volume increased to 6.6513nm and 0.971902cm 3 / g. The HA wrapping reduces the roughness of the nanoparticles, covers part of the original pores, and forms some new pores, so the specific surface area increases to 610.3903m 2 / g, the pore diameter and pore volume did not change much, which were 6.996nm and 0.926611cm 3 / g.
[0132] Example 6: Analysis of particle size, zeta potential and thermogravimetric analysis
[0133] Method: The particle size, Zeta potential and thermogravimetric analysis of MSN, MSN-NH2, MSN-PDA-CS-mPEG and HA@MSN-PDA-CS-mPEG in Example 1 were performed.
[0134] The particle size and zeta potential were measured by a British Zetasizer Nano ZS90 instrument (Malvern, UK). Thermogravimetric analysis (TGA) was performed using a TGA Q550 instrument (TA, USA) under N2 atmosphere at a speed of 10 K / min.
[0135] Results: Figure 4 As shown in a, the average particle size of MSN is about 105 nm. Each step of modification will increase the particle size. The average particle sizes of MSN-NH2, MSN-PDA-CS-mPEG, and HA-MSN-PDA-CS-mPEG ammonia are 122 nm, 141 nm, and 190 nm, respectively.
[0136] like Figure 4As shown in b, the characterization of Zeta potential further demonstrated the continuous change of Zeta potential during the preparation of nanodrug carriers, proving the successful modification of the copolymer and hyaluronic acid.
[0137] The thermogravimetric loss rate of the samples after each step of modification was compared. Figure 4 As shown in Figure c, the weight loss rate of MSN is 8.26%, and the weight loss rate of MSN-NH2 increases to 21.78%. The introduction of PDA, CS, mPEG and HA makes the thermogravimetric loss rate of MSN-PDA-CS-mPEG and HA@MSN-PDA-CS-mPEG gradually increase to 24.91% and 45.07%, respectively.
[0138] Example 7: Infrared spectrum analysis
[0139] Methods: The MSN, MSN-NH2, MSN-PDA-CS-mPEG, and HA@MSN-PDA-CS-mPEG in Example 1 were tested for Fourier transform infrared spectroscopy (FT-IR) on a Nicolet iS50 spectrophotometer (Thermo Fisher Scientific, USA).
[0140] Results: Figure 5 As shown, the infrared spectrum shows the interconnection between the functional groups in each modification process of MSN, proving that the desired drug carrier is synthesized.
[0141] Example 8: Preparation of Astragalus Polysaccharide (APS) Standard Curve
[0142] Methods: 30 mg of Astragalus polysaccharide (APS) was accurately weighed and prepared into a 0.5 mg / mL stock solution for standby use. It was then diluted into a series of solutions with concentration gradients: 0.05 mg / mL, 0.10 mg / mL, 0.15 mg / mL, 0.20 mg / mL, 0.25 mg / mL, 0.30 mg / mL, 0.35 mg / mL, 0.40 mg / mL, 0.45 mg / mL. The absorbance of different drug concentrations at 281 nm was measured by UV-Vis, and the APS standard curve equation was determined by linear fitting.
[0143] Results: Figure 6 As shown, the APS standard curve equation is A = 2.1021C-0.002R 2 =0.9944.
[0144] Example 9: Analysis of HA@MSN-PDA-CS-mPEG drug loading performance
[0145] (1) Methods
[0146] Astragalus polysaccharide (APS) was prepared into solutions of different concentrations (0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL, 1.0 mg / mL, ..., 2.6 mg / mL, 2.7 mg / mL) using ultrapure water.
[0147] The HA@MSN-PDA-CS-mPEG nanocarrier was prepared into a 2 mg / mL solution with ultrapure water, and ultrasonicated for 20 min to make it evenly dispersed to obtain a nanocarrier solution.
[0148] APS solutions of different concentrations were added to the nanocarrier solution, with the volume ratio of the nanocarrier solution to the APS solution being 1:1. The mixed solutions were prepared respectively, and the obtained mixed solutions were ultrasonicated for 20 min to make them evenly mixed. The mixed solutions were stirred at 700 r / min in the dark at room temperature for 24 h, and centrifuged at 10000 rpm for 10 min to achieve the effect of solid-liquid separation, thereby obtaining a precipitate and a supernatant.
[0149] The obtained precipitate was washed by centrifugation, and ultrapure water and anhydrous ethanol were used as detergents. The ultrapure water and anhydrous ethanol were washed three times each, and each centrifugation was centrifuged at a speed of 10000r / min for 10min. The free drugs and surface adsorbed drugs were washed with ultrapure water and anhydrous ethanol to obtain drug-loaded nanoparticles HA-APS@MSN-PDA-CS-mPEG. The supernatant was collected and the drug absorbance at 281nm was measured. The drug loading rate was then calculated according to the formula:
[0150]
[0151] Among them, W z is the total mass of APS added; W s is the mass of APS in the supernatant; W t is the total mass of the carrier and the drug after drug loading.
[0152] Results: Figure 7 As shown, the drug loading rate increases with the increase of drug concentration. When the APS concentration rises to 0.95 mg / mL, the drug loading rate reaches a peak value of 28.5%.
[0153] Example 10: Analysis of drug release properties of HA@MSN-PDA-CS-mPEG
[0154] Method: The nano drug delivery system prepared by the method of Example 1
[0155] HA-APS@MSN-PDA-CS-mPEG was dispersed in 2 mL PBS solution (pH = 7.4), added to a dialysis bag after ultrasonic treatment, and then transferred to 40 mL PBS buffer solution containing different components. The pH variables were controlled at 7.4, 6.5 and 5.0, respectively, to study the effect of pH on the sustained release of drugs. The sample solution was irradiated with 808 nm near-infrared laser to study the effect of near-infrared irradiation on the sustained release of drugs.
[0156] Place it in a constant temperature shaking incubator and shake it at a rate of 100 rpm. Take 3 mL of the release solution at 0.5 h, 1 h, 2 h, 3 h, 4 h, 6 h, 8 h, 10 h, 12 h, 24 h, 36 h, 48 h, 60 h, 72 h, 84 h, and 96 h, and add an equal volume and concentration of sustained-release solution. Measure its absorbance with UV-Vis, and calculate the cumulative drug release rate of the drug carrier according to the following formula:
[0157]
[0158] The obtained data was imported into Origin for processing to obtain the results.
[0159] Results: Figure 8 As shown in the figure, the decrease of pH and near-infrared irradiation will lead to an increase in the drug release rate of nanoparticles. When the pH value is 7.4, 6.5, and 5.0, the release of APS after 96 hours is 45.01%, 48.79%, and 53.37%, respectively. After adding near-infrared, the release of APS under pH 7.4, 6.5, and 5.0 conditions increased to 48.14%, 57.87%, and 64.31%, respectively, indicating that HA-APS@MSN-PDA-CS-mPEG has pH responsiveness and photothermal synergy.
[0160] Example 11: Photothermal performance test of nanomaterials
[0161] Method: HA@MSN-PDA-CS-mPEG prepared in Example 1 with different concentrations was used at a power density of 2 W / cm 2 The power density of HA@MSN-PDA-CS-mPEG was 2W / cm 2 The film was irradiated to 42 °C and then cooled to room temperature for 5 cycles, with the temperature recorded every 15 s to determine the photothermal stability.
[0162] Results: Fig. 9 As shown in a, at the same concentration, as the laser irradiation time increases, the color of the image gradually becomes lighter, indicating that the temperature of the material gradually increases, proving that the prepared nanomaterial has a photothermal effect. Fig. 9As shown in Figure b, a 500 μg / mL nanoparticle solution was heated from 25°C to 47°C and then naturally cooled to 25°C. The illumination heating-natural cooling cycle was repeated 5 times. The time taken for the 5 cycles was basically the same, indicating that the nanoparticles have good photothermal stability.
[0163] Example 12: Hemolytic Test of Nanoparticles
[0164] Methods: Hemolysis experiments were performed on the synthesized nanoparticles using defibrinated sheep blood to evaluate the biocompatibility of MSN, MSN-PDA-CS-mPEG, HA-@MSN-PDA-CS-mPEG, and HA-APS@MSN-PDA-CS-mPEG prepared in Example 1.
[0165] Results: Fig.10 As shown, the hemolysis rate of the modified mesoporous silica is less than 5%, which has good biocompatibility.
[0166] Example 13: Cytotoxicity test
[0167] Methods: A549 cells were seeded in a 96-well plate at 5000 cells / well and incubated with different concentrations of MSN, HA-@MSN-PDA-CS-mPEG, HA-APS@MSN-PDA-CS-mPEG and HA-APS@MSN-PDA-CS-mPEG+NIR prepared in Example 1 for 24 h. Cell viability was detected by CCK-8 method. The toxicity of the material to the cells after treatment was determined by comparing the cell viability to determine the optimal drug carrier concentration, and the cell survival rate was calculated according to the formula:
[0168] Cell survival rate (%) = [(OD1-OD0) / (OD2-OD0)] × 100
[0169] Wherein: OD1 is the absorbance of the experimental group; OD2 is the absorbance of the control group; OD0 is the absorbance of the blank group.
[0170] Drug administration group: cells+nanoparticles+culture medium+CCK-8.
[0171] Control group: cells+culture medium+CCK-8.
[0172] Blank group: culture medium + CCK-8.
[0173] Results: Fig.11 As shown, HA@MSN-PDA-CS-mPEG nanocarriers have good biocompatibility, while HA-APS@MSN-PDA-CS-mPEG can effectively kill tumor cells.
[0174] In combination with the embodiments, it can be seen that the present invention uses typical nanocarrier mesoporous silica as a carrier, and PDA, CS, and mPEG form copolymer micelles and then coat them on the surface of silica spheres, so that it has good photothermal conversion efficiency, good pH sensitivity, and excellent biocompatibility, water solubility and transportation capacity in the near-infrared region; subsequently, a layer of HA is coated on the surface of the nanoparticles to avoid the adsorption of most blood proteins on the surface of the nanoparticles, thereby prolonging the circulation time of the nano-drug delivery system in the body, and the differentiation cluster protein C4DD of tumor cells serves as the main receptor of HA, so that the HA-modified drug delivery system successfully enters the tumor cells through endocytosis; astragalus polysaccharide, a traditional Chinese medicine active molecule that can enhance the drug effect, is loaded on it, and a nano-drug delivery system HA-APS@MSN-PDA-CS-mPEG with pH sensitivity, long circulation, good biocompatibility and photothermal effect is successfully prepared for the adjuvant treatment of lung cancer.
[0175] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in the present embodiment to express the dosage, percentage, and other numerical values should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification and the attached claims are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained according to the reported significant figures and by conventional rounding methods.
[0176] The above is only a preferred embodiment of the embodiment of the present invention, and does not impose any form of limitation on the embodiment of the present invention. Any simple modification, equivalent changes and modifications made to the above embodiment based on the technical essence of the embodiment of the present invention are still within the scope of the technical solution of the embodiment of the present invention.
Claims
1. A method for preparing HA-APS@MSN-PDA-CS-mPEG nanoparticles, characterized in that: The following steps are involved: (1) Preparation of mesoporous silica microspheres; (2) Amino modification: the mesoporous silica microspheres are subjected to amino modification to obtain MSN-NH2; (3) coating the MSN-NH2 with a PDA-CS-mPEG copolymer to obtain MSN-PDA-CS-mPEG; (4) Hyaluronic acid modification: The MSN-PDA-CS-mPEG is modified with hyaluronic acid to obtain HA@MSN-PDA-CS-mPEG; (5) Loading astragalus polysaccharide: The HA@MSN-PDA-CS-mPEG and astragalus polysaccharide are mixed evenly in an aqueous solution, stirred and reacted for 22-26 hours in a dark environment, and then solid-liquid separation, centrifugal washing, and freeze-drying are performed to obtain the HA-APS@MSN-PDA-CS-mPEG nanoparticles.
2. The preparation method according to claim 1, characterized in that: The process of preparing mesoporous silica microspheres in step (1) is as follows: dissolving CTAB and ammonia water in water until clear, adding ethanol solution and stirring until uniformly mixed, then dropping tetraethyl silicate and reacting for at least 48 hours, adding methanol at 75-85° C. to promote precipitation, solid-liquid separation, centrifugal washing, vacuum drying, calcination, and cooling to room temperature; The amino modification process in step (2) is as follows: dissolving the mesoporous silica microspheres in toluene, adding 3-aminopropyltriethoxysilane, mixing evenly, adding triethylamine, reacting at 110-130° C. for at least 5 hours, separating the solid from the liquid, washing by centrifugation, and freeze-drying; The coating process in step (3) is as follows: dissolving the PDA-CS-mPEG copolymer and the MSN-NH2 in water, stirring the reaction in the dark, separating the solid from the liquid, washing by centrifugation, and freeze-drying.
3. The preparation method according to claim 2, characterized in that: The mass volume ratio of the mesoporous silica microspheres to toluene and 3-aminopropyltriethoxysilane in step (2) is 390-410 mg: 40 mL: 1.8 ml; In the step (3), the mass ratio of MSN-NH2 and PDA-CS-mPEG copolymer is 1:0.8-1.
2.
4. The preparation method according to claim 3, characterized in that: The mass volume ratio of the mesoporous silica microspheres to toluene and 3-aminopropyltriethoxysilane in step (2) is 400 mg: 40 mL: 1.8 ml; In the step (3), the mass ratio of MSN-NH2 and PDA-CS-mPEG copolymer is 1:
1.
5. The preparation method according to claim 1, characterized in that: The preparation method of the PDA-CS-mPEG copolymer in the step (3) is as follows: 1-hydroxybenzotriazole and 1-ethyl-(3-dimethyl-amino-propyl)carbodiimide are uniformly dispersed in water, PDA, CS, and mPEG-COOH are added, and the mixture is stirred in the dark to react, and then extracted with a dichloromethane solution as an extractant, and then rotary evaporated at 55-65° C. and freeze-dried.
6. The preparation method according to claim 5, characterized in that: The mass ratio of 1-hydroxybenzotriazole, 1-ethyl-(3-dimethyl-amino-propyl)carbodiimide, PDA, CS, and mPEG-COOH is 1:2:1:1:
6.
7. The preparation method according to claim 1, characterized in that: The process of hyaluronic acid modification in step (4) is as follows: adding the MSN-PDA-CS-mPEG to the activated hyaluronic acid solution, stirring at room temperature for 23-26 hours, separating the solid and liquid, washing by centrifugation, and drying in vacuo; The preparation method of the activated hyaluronic acid solution is as follows: hyaluronic acid is uniformly dispersed in PBS buffer, and EDC and NHS are added to activate it; In the step (5), the mass ratio of HA@MSN-PDA-CS-mPEG to astragalus polysaccharide is 1.4-2:
2.
8. The preparation method according to claim 7, characterized in that: In the step (4), the mass ratio of hyaluronic acid to MSN-PDA-CS-mPEG is 1.5:0.30-0.4; In the step (5), the mass ratio of HA@MSN-PDA-CS-mPEG to astragalus polysaccharide is 1.9:
2.
9. The preparation method according to claim 8, characterized in that: In the step (4), the mass ratio of hyaluronic acid to MSN-PDA-CS-mPEG is 1.5:0.
35.
10. A HA-APS@MSN-PDA-CS-mPEG nanoparticle, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Cited By
HA / CS / dECM-AD hydrogel medicine and application thereof in treatment of osteoarthritis
CN120678717A